Management of the motor disorders of children with cerebral palsy (Mac Keith,Distributed by Cambridge University Press, 2004)
Therapists, trainee and established neurodevelopmental paediatricians and paediatric neurologists will all find this text an extremely useful and thorough grounding in this subject...very useful when talking to parents and older children about their difficulties and any proposed management plan